Reflections on the sequence of musical development. Issue 1 (March 2022) - Swanwick, Keith
Abstract: The sequence of musical development is revisited. The origins of the underlying and evolving theory are considered, along with organisation and classification of the data of children's compositions. The cumulative and recursive nature of the spiral is re-emphasised, and the dynamic relationship between the left and right side is clarified. The essential qualitative nature of the study is asserted and some possibilities for the future are considered, along with a two-dimensional model for curriculum and student evaluation based on spiral-related outcomes and the musical activities that promote and sustain them.